Glycolic acid-functionalized chitosan-Co3O4-Fe3O4 hybrid magnetic nanoparticles-based nanohybrid scaffolds for drug-delivery and tissue engineering - Kumari, Sangeeta; Singh, Raj Pal (Journal of Materials Science, 2013)
In the present work, Co3O4 was prepared by hydrothermal process, which is further used for the synthesis of Co3O4-Fe3O4 hybrid nanoparticles. The formation of Co3O4-Fe3O4 nanoparticles was investigated by transmission electron microscopy and physical property measurement system. In the next step, the drug-loaded novel nanohybrid porous scaffold based on chitosan-g-glycolic acid and Co3O4-Fe3O4 nanoparticle was prepared by freeze drying technique. The grafting of glycolic acid on chitosan drug loading in porous scaffold was characterized by Fourier transform infrared spectroscopy. The nanohybrid scaffolds were found to be stable regardless of the pH of the medium and play an important role in cell adhesion, proliferation, and migration. Co3O4-Fe3O4 hybrid nanoparticles' reinforcement was found to control the drug (cyclophosphamide) release rate in phosphate buffer saline solution (pH 7.4). Therefore, Co3O4-Fe3O4 hybrid nanoparticles are viable additives for formulating sustained drug delivery systems and could be applied in the field of biomaterials.